Pengaruh Promosi, Kualitas Pelayananan dan Persepsi Harga Terhadap Keputusan Menginap di Whiz Hotel Cikini Jakarta - eliya rachmawati; hariadi hadiswarno (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
In the hospitality industry, consumer purchasing decisions are the most important aspect of company life because they can affect profitability, especially Whiz Hotel Cikini. This study aims to analyze the effect of promotion (X₁), service quality (X₂), and perceived price (X₃) as intervention variables on the decision to stay (Y) at Whiz Hotel Cikini. This study uses a quantitative research design using survey methods and accidental sampling. Participants consisted of (n = 90) individuals who had made purchases at Whiz Hotel Cikini. The data gathered from survey participants was subjected to multiple regression analysis for analysis purposes. The primary data was directly acquired from the respondents. Based on the results of the study, it shows that promotion (X₁), service quality ((X₂), and perceived price (X₃) have a significant effect on the decision to stay (Y) simultaneously, while promotion (X₁), partially has no positive and insignificant effect on the decision to stay (Y), and the results of the study show that service quality (X₂) has a positive and significant effect on the decision to stay (Y), and perceived price (X₃) has a significant positive effect on the decision to stay (Y) at Whiz Hotel Cikini. In summary, it can be inferred that factors such as promotional activities, the quality of service, and the perceived price play a crucial role in determining customers' choice to continue their stay at Whiz Hotel Cikini.